1992
DOI: 10.1139/v92-187
|View full text |Cite
|
Sign up to set email alerts
|

Molecular recognition XII. The binding of the H human blood group determinants and congeners by a lectin of Galactiatenuiflora

Abstract: 70. 151 1 (1992).The H-type 2 human blood group-related trisaccharide (a-L-Fuc-(lcj2b)-P-D-Gal-(] b4a)-P-D-GlcNAc-OMe (52)) IS bound by the anti-H lectin of Galnctin tenuiflora very differently than by the lectin I of Ulex europaeus. The reason why the Galactia lectin binds the H-type 1 related trisaccharide (a-~-Fuc-(lc~2b)-~-~-Gal-(lb3a)-~-~-GlcNAc-OMe (5)) more strongly and methyl a-L-fucopyranoside much more weakly than does the U1e.r lectin is that, for the Galactia lectin, the hydroxyl groups at position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…On the basis of this information the changes in the thermodynamic parameters caused by various structural modifications are examined in terms of the observed enthalpy*ntropy compensations. As was found in several other cases (5)(6)(7), the surface of 1 that is recognized by WBA I1 is relatively small and polyamphiphilic.…”
Section: Ohsupporting
confidence: 75%
See 2 more Smart Citations
“…On the basis of this information the changes in the thermodynamic parameters caused by various structural modifications are examined in terms of the observed enthalpy*ntropy compensations. As was found in several other cases (5)(6)(7), the surface of 1 that is recognized by WBA I1 is relatively small and polyamphiphilic.…”
Section: Ohsupporting
confidence: 75%
“…The radioimmunoassays were performed according to a published procedure ( I 3). The plastic tubes were coated using a solution of WBA-I1 (100 pg/mL) in 0.1 N phos- Except for the mono-0-methyl derivatives of 1 that are presented in Table 1, the syntheses of the various other congeners used in this study have already been reported (6,7,14). The mono-0-methyl derivatives were prepared following procedures similar to those used for the synthesis of 0-methyl derivatives of the Lewis b tetrasaccharide (4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The disaccharide 1-deoxy-3-0-(a-D-glucopyranosy1)-mannojirimycin (9) has been shown to strongly inhibit the action of endo-a-D-mannosidase ( l ) , a glycoprotein-processing hydrolase that releases aDGlc(l+ 3 )~M a n from incompletely deglucosylated GlcMan,GlcNAc, oligosaccharide of immature N-linked glycoproteins (2,3). Although deoxymannojirimycin itself is known to be a strong exomannosidase inhibitor (4), it was found inactive towards endo-mannosidase (3).…”
Section: Introductionmentioning
confidence: 99%
“…It is to be noted in this regard that extensive protein-oligosaccharide binding studies have been performed with numerous lectins (5)(6)(7)(8)(9). monoclonal antibodies (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%